Analysis of Coffee Production Response to Increasing Coffee Prices in South OKU Regency - Marliyani Marliyani; Munajat Munajat; Yetty Oktarina (Tropical Plantation Journal, 2026)
Coffee is a vital plantation commodity in the national economy. South OKU Regency has emerged as the leading coffee producer in South Sumatra Province, with a total production of 50,854 tons. This study aims to analyze the production response toward the increase in coffee prices in South OKU Regency. The hypothesis in this study was tesed using multiple linear regression analysis. Based on the results of the coefficient of determination (Model Summary), an R-Square value of 0.812, or 81.2 percent, was obtained. This value indicates that the variables of land area ($X_1$), fertilizer quantity ($X_2$), production ($X_3$), and pesticides ($X_4$) collectively explain 81.2 percent of the variation in coffee price changes ($Y$) in South OKU Regency. Meanwhile, the remaining 18.8 percent is influenced by other factors not accounted for in the model.